ФОРМУВАННЯ І РОЗВИТОК ІДЕЙНОГО ЗАДУМУ В КОМПОЗИЦІЇ ТА ЕТАПИ ТВОРЧОГО ПРОЦЕСУ (Педагогіка вищої та середньої школи, 2022)
The article winch is written on the difficult problem of creative work (stages of creative process). The author shows the ideal think of the composition.